The effects of practice scheduling on the learning of ultimate frisbee throws in skilled players - Suratos, Danielle Arcilla 2000-
The contextual interference (CI) effect is a motor learning phenomenon that explains that increasing the level of variation during practice of a motor skill improves one’s performance of a skill. Random practice is a type of repetition pattern that has higher CI where skills are practiced randomly instead of in blocks. Although the effects of random practice on novice players have been explored, there is a lack of investigation of the effects of random practice on skilled players who practice an open-loop skill. This study aimed to investigate the effects of random practice on the throwing accuracy of skilled Ultimate Frisbee players. The experimental research included ten (10) Ultimate Frisbee players (male and female) who have been playing the sport competitively for over two (2) years. The participants were divided into two (2) groups: a blocked practice group (control) and a random practice group. Each group underwent three (3) different sessions where their throwing accuracy was tested with an accuracy test patterned after a test done by Entezari et al. in 2017. It was hypothesized that the random group would have a significant positive change to their throwing accuracy after the intervention. At a level of significance of o = 0.05, the study found that there was no significant difference in within-group paired t-tests for retention (random practice group: p = 0.37; blocked practice group: p =0.37) or transfer (random practice group: p=0.34 , p = 0.19; blocked practice group: p=0.09, p =0.13). The results also showed that there was no significant difference in between-group independent t-tests for the practice session (p = 0.71), retention test (p = 0.15) and transfer test (p = 0.44). The results of this study may help sports professionals (players and coaches) better understand how to maximize training times for better performance during competitive games.